Typological Characteristics of Websites of Regional Mass Media (by the Example of the Republic of Tatarstan) - T.S. Staroverova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The relevance of the study is determined by the low exploration degree of the typological characteristics of websites of regional mass media. The object of research is websites as a new form of contemporary mass media. The attention is focused on the specificity of forms and types of websites of regional mass media. The empirical basis is mass media of the Republic of Tatarstan. The aim of the research is to identify the typological characteristics of websites of regional mass media. To achieve this aim, the following tasks are set: 1) to single out criteria for typologization (classification) of websites of regional mass media; 2) to carry out a comparative analysis of the typological groups of websites of regional mass media. The main research methods used are structural and functional analysis, analysis of theoretical sources, and comparative analysis. The obtained results can be helpful in educating future journalists specializing on Internet journalism and serve as a basis for more comprehensive investigation. A classification is suggested with regard to the following five criteria developed based on the analysis of theoretical sources: 1) availability of a non-networked version of the mass media means; 2) official status of information; 3) degree of interactivity; 4) signs of being the main mass media means, including repetition of names and thematic focus of sections, similarity in design and its elements, stylistic features of text writing; 5) professional nature of journalism based on qualitative assessment of allocated texts. According to these characteristics, all websites of regional mass media, in the author’s opinion, can be divided into the following typological groups: 1) official websites; 2) home pages; 3) groups in social networks; 4) information portals; 5) corporate websites.